General Self-Efficacy and Body Weight: The Role of Race and Gender. Issue 6 (December 2021) - Schmidt, Gordon; Pichler, Shaun
Overweight and obesity have become a prominent concern for policymakers, the Surgeon General, scholars, and for work organizations. The estimated annual cost of obesity in terms of lost productivity is in the tens of billions of dollars, and the estimated annual medical cost of obesity is in the hundreds of millions of dollars. Psychologists have become increasingly interested in issues related to body weight, such as ways to help people reduce body weight. The aims of our study are twofold. First, based on social cognitive theory, we offer the first study of the relationship between general self-efficacy (GSE) and body weight based on a large, representative sample. Second, we also offer an understanding of the role of race and gender as potential boundary conditions of this relationship. Findings indicate that race moderates the relationship between GSE and body weight (both BMI and perceived weight) such that this relationship is positive for Blacks but negative for Whites. Gender did not moderate the relationship between GSE and body weight. These results suggest that body weight is unrelated to general self-efficacy in the population writ large and that body weight is differentially related to self-efficacy based on race but not gender.